Conjugation of mono and di-GalNAc sugars enhances the potency of antisense oligonucleotides via ASGR mediated delivery to hepatocytes. Issue 15 (1st August 2016) - Kinberger, Garth A.; Prakash, Thazha P.; Yu, Jinghua; Vasquez, Guillermo; Low, Audrey; Chappell, Alfred; Schmidt, Karsten; Murray, Heather M.; Gaus, Hans; Swayze, Eric E.; Seth, Punit P.
Graphical abstract: Abstract: Antisense oligonucleotides (ASOs) conjugated to trivalent GalNAc ligands show 10-fold enhanced potency for suppressing gene targets expressed in hepatocytes. Trivalent GalNAc is a high affinity ligand for the asialoglycoprotein receptor (ASGR)—a C-type lectin expressed almost exclusively on hepatocytes in the liver. In this communication, we show that conjugation of two and even one GalNAc sugar to single stranded chemically modified ASOs can enhance potency 5–10 fold in mice. Evaluation of the mono- and di-GalNAc ASO conjugates in an ASGR binding assay suggested that chemical features of the ASO enhance binding to the receptor and provide a rationale for the enhanced potency.